2016
DOI: 10.1002/cbic.201500551
|View full text |Cite
|
Sign up to set email alerts
|

The Casein Kinase 2‐Dependent Phosphorylation of NS5A Domain 3 from Hepatitis C Virus Followed by Time‐Resolved NMR Spectroscopy

Abstract: Hepatitis C virus (HCV) chronically affects millions of individuals worldwide. The HCV nonstructural protein 5A (NS5A) plays a critical role in the viral assembly pathway. Domain 3 (D3) of NS5A is an unstructured polypeptide responsible for the interaction with the core particle assembly structure. Casein kinase 2 (CK2) phosphorylates NS5A-D3 at multiple sites that have mostly been predicted and only observed indirectly. In order to identify the CK2-dependent phosphorylation sites, we monitored the reaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(132 reference statements)
2
4
0
Order By: Relevance
“…Globally in the NS5A-D1D2D3 sample, the phosphorylation levels are 33%, 100%, 62%, 77%, 63%, 67%, 67%, 67% and 64% for the residues Ser 401 , Ser 408 , Ser 412 , Ser 415 , Ser 429 , Ser 432 , Ser 434 , Thr 435 , and Ser 437 respectively. Our results are in line with a recent study showing that in vitro the casein kinase 2 quickly phosphorylates S408 in NS5A-D3, whereas S401, S429, and S434 are more slowly and less efficiently modified . Despite the presence of numerous serine and threonine residues in LCS1-domain2 and despite the fact that phosphorylations have already been reported in these regions, , we did not detect any phosphorylation here by NMR spectroscopy.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Globally in the NS5A-D1D2D3 sample, the phosphorylation levels are 33%, 100%, 62%, 77%, 63%, 67%, 67%, 67% and 64% for the residues Ser 401 , Ser 408 , Ser 412 , Ser 415 , Ser 429 , Ser 432 , Ser 434 , Thr 435 , and Ser 437 respectively. Our results are in line with a recent study showing that in vitro the casein kinase 2 quickly phosphorylates S408 in NS5A-D3, whereas S401, S429, and S434 are more slowly and less efficiently modified . Despite the presence of numerous serine and threonine residues in LCS1-domain2 and despite the fact that phosphorylations have already been reported in these regions, , we did not detect any phosphorylation here by NMR spectroscopy.…”
Section: Resultssupporting
confidence: 92%
“…From a structural point of view, the present NMR analyses revealed that phosphorylations do not change the disordered nature of D2 and D3 domains but multiply the number of conformers due to partial phosphorylations. In line with our results, Secci et al have concluded that the phosphorylation of pS401, pS408, pS429, and pS432 in NS5A-D3 do not influence its secondary structure content . Differential phosphorylation patterns could give rise to a huge number of NS5A phosphovariants probably serving various functions .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…By exploiting the non-destructive and quantitative nature of such NMR measurements, we illustrated another analytical advantage of this approach: The ability to directly follow PTM reactions in a time-resolved fashion in order to deduce site-specific modification rates [97,98]. Indeed, protein phosphorylation studies by time-resolved NMR spectroscopy became very popular and proved essential for delineating mechanistic insights into diverse sets of signaling reactions [99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135].…”
Section: Detecting Post-translational Protein Modifications By Nmrmentioning
confidence: 99%